Multimodal Imaging in Ocular Tuberculosis. (2nd January 2017) - Agarwal, Aniruddha; Mahajan, Sarakshi; Khairallah, Moncef; Mahendradas, Padmamalini; Gupta, Amod; Gupta, Vishali
ABSTRACT: Intraocular tuberculosis presents a diagnostic challenge because of its protean clinical manifestations. Thus, it becomes imperative to distinguish chorioretinal inflammation due to tuberculosis from other infectious as well as non-infectious posterior uveitis since the clinical manifestations of these entities may be quite similar. With advancing technology, a number of novel imaging modalities are available today that enable in vivo near-histologic assessment of the chorioretinal tissue, greatly aiding the clinician in establishing a diagnosis and monitoring the therapeutic response of tubercular lesions. Techniques such as ultra-wide field fundus photography, fluorescein and indocyanine green angiography, optical coherence tomography and most recently, optical coherence tomography angiography, provide valuable information that helps in advancing our knowledge regarding the pathogenesis and natural history of the disease. The index review describes how these techniques supplement each other, and highlights the relevance of multimodal imaging in the management of intraocular tuberculosis.